PENGARUH PERILAKU ETIS DAN ORIENTASI PELANGGAN TERHADAP KINERJA TENAGA PENJUAL SEBUAH STUDI PADA INDUSTRI ASURANSI JIWA DI SEMARANG - Sutopo, Sutopo; Sutono, Sutono (JURNAL BISNIS STRATEGI, 2004)
Professionalism in the field of selling represent the successful key of future marketing. Salesperson which protesional is a able to be trusted and always try to give the maximal satisfaction to customer. Trust and satisfaction of customer can only be reached if salesperson owning ethical behavior and customer orientation in running aclivily and sales strategy so the can improve the sales revenue. This research test how ethical.behavior and customer orientation influence to makeÂup outcome performance by passing behavior performance of salesperson.Data was gained from 120 life insurance agent as respondent in Semarang Central Java. From data analysis, result was obtained, model raised in this research in accepable. It is shown by chiÂquare = 105, 779, Probability = 0, 32 7, Root Mean Square Error of Approximation = 0, 022, Goodness of Fit Index= 0,904, Adjusted Goodness of Fit Index= 0,870, Tucker Lewis Index = 0, 994, CMIN/DF = 1, 058, Comparative Fit lndexs = 0,995. Those number indexs are standart although Adjusted Goodness of Fit Index is accepted marginally. Findings show that hig outcome performance salesperson can be achieved with ethical behavior and costumer olientation by increasing behavior performance. Cocludes with a discussion of managerial implications and direction for future reserch.